Competencies of Using Computers in Teaching: An Evaluative Study on Students of the Faculty of Education, Sohag University - Saleh, Shoeb Gamal; AlAli, Rommel Mahmoud; Mashal, Anees Abdullatif (Journal of Ecohumanism, 2024)
This study aimed to assess the competencies of Sohag University’s Faculty of Education students in computer-based teaching competencies, employing a descriptive-analytical approach and a questionnaire covering eight core areas: the role of computers in education, information technology skills, integration of computers in teaching, use of the internet and email for instruction, operation of Windows OS, utilization of presentation software, spreadsheets, and word processing tools. A cognitive achievement test was also developed to measure students’ knowledge in these areas, with a sample comprising 235 students from both scientific and literary disciplines. The findings revealed varied student perceptions regarding the impact of their academic studies on developing computer-based teaching skills, with statistically significant differences (p ≤ 0.01) favoring scientific students over literary students in both their questionnaire responses and test performance. Additionally, students generally exhibited low competency scores on the test, highlighting the need for enhanced focus on practical skill development. A positive correlation (r = 0.26) was also identified between literary students’ questionnaire responses and their test performance, statistically significant at the 0.01 level, underscoring the importance of bridging the gap between theoretical knowledge and practical application.